The Effect Of Online Consumer Review And Prices On Online Purchase Decisions - Nur Aisyah Buana Putri; Agus Syam; Mustari Mustari; Muhammad Dinar; Muh. Ihsan Said; Muhammad Jufri (PINISI Discretion Review, 2022)
This study aims to determine the effect of online consumer reviews and prices on online purchasing decisions for students of the Faculty of Economics and Business, Makassar State University. The research method used is the quantitative method with the method of collecting data, namely through observation, questionnaires and documentation. In this survey, the majority of respondents are students who have made online purchases, and overall there are 97 respondents. The data collection methodology used a questionnaire instrument that was compiled based on a Liker scale and had gone through validation and reliability procedures. The analysis was then performed using multiple linear regression analysis. The results showed that: 1) Partially the online consumer review variable had a positive and significant effect on online purchasing decisions for students of the Faculty of Economics and Business, Makassar State University. 2) Partially, the price variable has a positive and significant effect on online purchasing decisions for students of the Faculty of Economics and Business, State University of Makassar. 3) Simultaneously online consumer reviews and prices have a positive and significant effect on online purchasing decisions for students of the Faculty of Economics and Business, State University of Makassar.